Governansi Digital Sebagai Strategi Peningkatan Partisipasi Masyarakat Dalam Kebijakan Publik - Mozin, Sri Yulianty; Bangko, Nia Rahmadani; Abdullah, Susanti; Sawali, Nadia; Daud, Fidyan; Juliawati, Ni Ketut (JPS: Journal of Publicness Studies, 2026)
Digital transformation in the public sector has led to the emergence of digital governance as a strategic approach to enhance public participation in public policy processes. The main issue addressed in this study is the low level of public participation due to limited access to information and communication between government and citizens. This study aims to analyze the role of digital governance in increasing public participation through the use of information and communication technology. The method used is a literature study by reviewing scientific journals from the last seven years. The results show that the implementation of digital governance through e-government platforms, social media, and public service applications can increase transparency, accountability, and citizen engagement in policymaking. However, challenges such as digital divide, technological literacy, and infrastructure remain obstacles. In conclusion, digital governance has great potential as a strategy to enhance public participation, but requires inclusive and sustainable policy support.